Evaluation of the antibacterial and efflux inhibitory activity of trans-cinnamic acid in Staphylococcus aureus: Experimental assays and in silico modeling - Nair Silva Macêdo; Zildene de Sousa Silveira; Débora Menezes Dantas; Cristina Rodrigues dos Santos Barbosa; Cícera Datiane de Morais Oliveira-Tintino; Saulo Relison Tintino; Gabriel Gonçalves Alencar; Gustavo Miguel Siqueira; Thaís Ferreira da Silva; Márcia Machado Marinho; Matheus Nunes da Rocha; Henrique Douglas Melo Coutinho; et al. (Phytomedicine Plus)
Background: Staphylococcus aureus develops bacterial resistance using membrane transport systems that perform the active efflux of antimicrobial agents, allowing its survival and growth. Objective: This study evaluated the antibacterial activity of trans-cinnamic acid and its ability to modify the antibiotic activity and inhibit the efflux pump mechanism present in the 1199B strain of S. aureus (NorA overexpressed). Methodology: The permeability of trans-cinnamic acid through the cytoplasmic membrane of S. aureus was also evaluated. In silico assays were used to evaluate the molecular interactions of this compound with the efflux protein NorA. Results: Trans-cinnamic acid did not show direct antibacterial activity against the 1199B strain of S. aureus. However, when combined with norfloxacin, it potentiated the antibiotic activity and reduced the MIC of norfloxacin. In addition, trans-cinnamic acid potentiated the effect of EtBr, reducing its MIC from 128 µg/mL to 64 µg/mL. The evaluated compound also increases membrane permeability in S. aureus strains, suggesting that this is one of the mechanisms of action involved in its activity. Molecular docking simulations showed that trans-cinnamic acid can act as an inhibitor of the NorA efflux pump due to its hydrophobic interactions with residues Tyr225 and Phe303. Pharmacokinetic descriptors showed that the compound presents good cell permeability due to the balance between lipophilicity and polarity favored by the presence of a deprotonated carboxylate group. Conclusion: In conclusion, trans-cinnamic acid has promising potential as an inhibitor of the resistance mechanism present in S. aureus and could act as a possible antibiotic adjuvant.